The Difference Between The Practice Of Passing Underhand The Ball Reflected On The Wall And The Ball Hanging On The Skill Of Passing Underhand Volleyball - Rumiati Rumiati; Setyo Harmono; Budiman Agung Pratama (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
The importance of lower passing in the game of volleyball to get the maximum achievement and considering the type of passing training program walled and passing using hanging balls is a method that can be used to improve passing underhand in volleyball games, this study aims to determine the effect of walled passing and passing exercises using hanging balls on lower passing skills at PGRI Jogorogo Junior High School, Ngawi Regency. This study uses a quantitative approach, the type of research is experimental research, the research design uses a randomized control group pretest-posttest, the sample is 39 people, while the data on volleyball passing underhand skills are collected using the lower passing test instrument. The data analysis technique used is an independent sample t-test. The results showed that the sig value of 0.001 < 0.05 which showed that there were differences in the method of passing exercises on the wall and passing using hanging balls against the bottom passing skills of volleyball, this was seen from the average value of the pretest and posttest of the walled passing group of 9.62 compared to the passing group using hanging balls with an average value of 4.31. Where is seen from the difference with an average value of 5,31.